2017
DOI: 10.1111/jne.12469
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal alterations in the daily rhythms in hypothalamic expression of genes involved in the photoperiodic transduction and neurosteroid‐dependent processes in migratory blackheaded buntings

Abstract: The present study investigated seasonal alterations in the daily rhythms of hypothalamic expression of genes involved in the photoperiodic regulation of annual cycles in birds. We measured the 4-hourly mRNA expression of genes involved in the photoperiodic transduction (OPN5, EYA3, CGA, TSHβ, DIO2, DIO3) and neurosteroid-dependent processes (AR, CYP19, ERα, ERβ) in the hypothalamus of migratory blackheaded buntings photoinduced with photosensitive, photostimulated (early and late stimulated) and photorefractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…In LD, birds exhibit fat deposition and weight gain, Zugunruhe (migratory restlessness; intense nocturnal activity and wing whirring in captive birds), and show elevated circulating concentrations of metabolites (e.g. glucose, triglycerides) and metabolic hormones, such as insulin and corticosterone (Agatsuma & Ramenofsky, ; Bairlein, ; Bartell & Gwinner, ; Fuchs, Haney, Jechura, Moore, & Bingman, ; Gwinner & Czeschlik, ; Mishra, Singh, & Kumar, ; Rani, Malik, Trivedi, Singh, & Kumar, ; Trivedi, Kumar, Rani, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LD, birds exhibit fat deposition and weight gain, Zugunruhe (migratory restlessness; intense nocturnal activity and wing whirring in captive birds), and show elevated circulating concentrations of metabolites (e.g. glucose, triglycerides) and metabolic hormones, such as insulin and corticosterone (Agatsuma & Ramenofsky, ; Bairlein, ; Bartell & Gwinner, ; Fuchs, Haney, Jechura, Moore, & Bingman, ; Gwinner & Czeschlik, ; Mishra, Singh, & Kumar, ; Rani, Malik, Trivedi, Singh, & Kumar, ; Trivedi, Kumar, Rani, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…birds fatten and gain weight, develop nocturnal Zugunruhe and show elevated plasma corticosterone, testosterone and luteinizing hormone (LH) concentrations and gonadal recrudescence (Jain & Kumar, 1995;Mishra et al, 2017;Misra et al, 2004;Rani et al, 2006). Hypothalamus and liver mRNA levels of the circadian clock and light-and thyroid hormone-responsive genes and of genes involved in carbohydrate and fat metabolism and oxidative phosphorylation show changes with alteration in the seasonal state (Mishra et al, 2017;Singh et al, 2015;Trivedi et al, 2014;Trivedi, Malik, Rani, & Kumar, 2015). We predicted transcriptome-wide changes in the hypothalamus and liver with photostimulation of the spring migratory state in black-headed buntings.…”
mentioning
confidence: 99%
“…We interpret this as a difference in the activation of apoptotic pathways, perhaps by p53 dependent cellular apoptosis (Jackson, Cho, Stein, & Liang, ), during LD‐induced states. Perhaps, there is the concurrent activation, albeit at different rates, of the molecular processes underlying the testicular maturation and the onset of photorefractoriness in buntings, as suggested by previous studies in other photoperiodic songbirds including canaries ( Serinus canarius ; Storey & Nicholls, ), European starlings ( Sturnus vulgaris ; Dawson, ) and redheaded buntings (Mishra, Bhardwaj, Malik, & Kumar, ). It is suggested that the exposure to a stimulatory photoperiod initiates concurrently the testicular maturation and development of refractoriness but at different rates: photostimulation of the testicular maturation is overridden by that of the development of photorefractoriness by a week of exposure to long days (Nicholls, Goldsmith, & Dawson, ; Storey & Nicholls, ).…”
Section: Discussionmentioning
confidence: 82%
“…All procedures were approved by the Institutional Animal Ethics Committee of the Department of Zoology, University of Lucknow (protocol no: LU/ZOOL/IRPHA/Protocol2.3/NOV07), where the experiment was done. We used testes from the experiment, as earlier described (Mishra, Singh, & Kumar, ; D. Singh, Trivedi, Rani, Panda, & Kumar, ). Briefly, adult male black‐headed buntings were maintained until the beginning (for about 40 weeks) of the experiment under short days (SD; 8L:16D, winter‐like photoperiod) in which they were unstimulated and photosensitive SDSE, or exposed to long days (LD, 16L:8D, summer‐like photoperiod) in which following testicular maturation cycle they were photorefractory, LDRF (similar to post‐breeding condition; D. Singh et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation